MOTORCYCLE RENTAL SMART SYSTEM DESIGN - Taufiqurrahman Taufiqurrahman; Lukman Effendi; Triana Harmini; Ilyasa Azmi (Program Studi Teknik Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an, 2022)
The need for transportation in the University of Darussalam Gontor (UNIDA Gontor) campus is currently in high demand. Therefore, the campus has provided motorbike rental services in the UNIDA Gontor Business Unit (U3) section of motorbike rental or U3 Motor. The problem in motorcycle rental management at U3 Motor at this time is the recording of rental transactions which still uses a manual system by recording in a notebook and then entering the data into Excel format. By looking at these facts, the researchers designed a smart information system for motorbike rental. This study aims to facilitate the reservation process for those who will rent a motorbike at U3 Motor. In addition, this smart system will facilitate the management of U3 UNIDA Gontor in managing transaction data and recording the circulation of incoming money obtained from the reservation process. This system design method uses the Software Development Life Cycle (SDLC) waterfall model which consists of several stages, which are requirements, analysis, design, implementation, and testing. The design of the data process design uses Use Case Diagrams and Data Flow Diagrams. While the database design uses Conceptual Data Model (CDM) and Physical Data Model (PDM). This system was developed using PHP programming language with yii2 framework and database using MySQL. Testing of this system is carried out using the black-box method on front-end and back-end applications. The test results on each page and function show that the system can work as expected. The results of this study indicate that the smart motorbike rental system is feasible to use to manage transaction data and record the circulation of incoming money obtained from the reservation process and is feasible to be developed to support the urban smart system network.